Pengaruh Pengalaman, Tekanan Ketaatan,Dan Pengetahuan Terhadap Audit Judgement Yang Diambil Oleh Auditor - Setiawan, Denny Mulyo; , Drs,Wahyono, Ak, MA (2015)
This study aimed to analyze the impact of variable experience, pressure obedience, and knowledge of auditors on the auditors judgment te study is to examine auditors of CPA in Surakarta and Yogyakarta. Data analysis method used in this research that includes data quality test validity and reliability test, the classic assumption test, which consists of normality test, multicollinearity, and heteroscedasticity test, test the hypothesis that includes multiple regression analysis test, test the accuracy of the model, statistical tests, and test detrminasi coefficient R². From research 7 Public Accountant Office of Surakarta and Yogyakarta obtained the number of samples that can be processed by 40 respondents. Based on the analysis of data using multiple regression analysis test can be concluded that the effect on the auditor's experience audit judgment, observance pressure effect on audit judgment, affect the auditor's knowledge of audit judgment. Keywords: auditor experience, stress obedience, and knowledge of auditors